Peran Orang Tua dalam Mengembangkan Kreativitas Anak Usia Dini pada Masa Pandemi Covid-19 - Malikatus Sholihah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
This research was conducted to find out how the role of parents in developing early childhood creativity during the COVID-19 pandemic. This study, using a qualitative descriptive approach, the research subjects involved RA Hidayatul Islamiyah students, parents, teachers, and school principals. Research data were collected by several techniques, such as observation, interviews, and documentation. The triangulation technique is carried out in order to be able to explore sources, namely by re-checking the information from interviews with documentation and observations and matching from one informant to other informants. The result of research on the role of parents in developing early childhood creativityduring the covid-19 pandemic, show that there are some parents who pay less attention to children’s activities at home, but there are also parents who work together with teachers to direct children to study at home in developing creativity through learning to cook cakes in the midst of the covid-19 pandemic. The conclusion of this study is that the role of parents who have a great desire in collaborating with teachers and to foster children learning to cook cakes at home can develop the creativity of earlychildhood especially during the covid-19 pandemic who conduct online learning (in the network)